Aboriginal social housing in remote Australia: crowded, unrepaired and raising the risk of infectious diseases. Issue 2 (May 2022) - Memmott, Paul; Lansbury, Nina; Go-Sam, Carroll; Nash, Daphne; Redmond, Andrew Martin; Barnes, Samuel; Simpson, Patrick (Pepy); Frank, Patricia Narrurlu
Abstract : Sufficient, well-maintained housing infrastructure can support healthy living practices for hygiene, safety and nutrition. This article focuses on the relationship between housing and health through a case study in the remote Barkly region in the Northern Territory, Australia. A research partnership between Anyinginyi Health Aboriginal Corporation and academic researchers employed a mixed methodological approach, involving interviews with residents, clinical and outreach staff, and clinical database analysis. The results revealed much higher levels of crowding in remote communities and in Tennant Creek than officially recorded, with up to 22 residents in surveyed households. Interviews with clinicians and public health staff highlighted the impact of crowding on infection transmission, poor sleep and reduced personal safety, and damage to health hardware. The database analysis detailed the types of preventable, hygiene-related infectious diseases that dominated, with over half of the total infectious disease diagnoses being skin, respiratory and ear, nose and throat infections. Repeated infection likely contributes to increased rates of chronic kidney and rheumatic heart diseases. The combined overall findings highlight the parallel conditions of the prevalence of hygiene-related infectious diseases, crowding and environmental health issues (including health hardware). No objective evidence of direct causal relationships was obtained due to the small scale and methodological limitations of the study. More complex future research is outlined in order to understand how to further investigate the burden of disease that the affects morbidity and mortality of Aboriginal Australians, and underlies the urgency for housing policy reform and funding to upgrade housing.